Examining the Role of Artificial Intelligence Chatbots in Enhancing University Students’ Interpersonal Skills and Academic Performance - Ayaz Ullah; Shazia Iqbal; Inayat Shah (Research Journal of Psychology, 2025)
This study explains how AI-powered chatbots can help university students in Pakistan improve their academic performance and social skills. It is set in a time when AI is changing the way schools work. A cross-sectional poll included 300 undergraduate students from a variety of socioeconomic backgrounds (57.3% male and 42.7% female). We employed standardized self-report instruments such as the Chatbot Engagement Scale, the Academic Self-Perception Subscale of the Student Adaptation to College Questionnaire, and the Interpersonal Competence Questionnaire. The results showed that pupils who used chatbots a lot did much better in school and improved their social skills more than students who didn’t use chatbots as much. There were no significant differences in academic achievement based on gender, but there were differences in how women and men interacted with one another, showing that cultural differences affect how chatbots help people express themselves and develop socially. Moderate favorable relationships were found between using chatbots, doing well in school, and growing as a person. These results support the use of AI chatbots as teaching tools that help with cognitive tasks and promote social and emotional growth, especially in situations when traditional classroom participation is limited by culture or logistics. We talk about what this means for Pakistani colleges’ policies on AI literacy, ethical use, and policy frameworks.